Impact of seasonal flux on 25‐hydroxyvitamin D and bone turnover in pre‐ and early pubertal youth. Issue 1 (February 2014) - Rajakumar, Kumaravel; Holick, Michael F; Moore, Charity G; Cohen, Elan; Olabopo, Flora; Haralam, Mary Ann; Bogusz, Jaimee; Nucci, Anita; Greenspan, Susan L
Abstract Background Seasonal fluxes in 25‐hydroxyvitamin D (25(OH)D) in children can affect bone turnover, and in turn potentially affect bone accrual and peak bone mass. The aim of this study was to examine the effect of seasonal flux on the association among 25(OH)D, parathyroid hormone (PTH) and markers of bone turnover in pre‐ and early pubertal black children and white children. Methods Data were collected during summer (June–September) and winter (December–March) in 6–12‐year‐old children. Measurements included serum 25(OH)D, PTH, osteocalcin (OC), collagen type 1 cross‐linked C‐telopeptide (CTx), dietary intake of vitamin D and calcium, skin color, sunlight exposure, and body mass index (BMI). Results A total of 138 children (mean age, 9.1 ± 1.7 years; black, n = 94; male, n = 81) were studied. 25(OH)D was higher (41.2 ± 13 vs 34.5 ± 11.1 ng/mL; P < 0.001) and CTx was lower (0.8 ± 0.3 vs 0.9 ± 0.5 ng/mL; P < 0.001) in all participants during summer when compared to winter. Furthermore, seasonal differences in CTx were more pronounced in black children (summer, 0.7 ± 0.3 vs winter, 1.0 ± 0.5 ng/mL; P < 0.001). PTH was a significant predictor of serum CTx and OC after adjusting for race, season, Tanner stage, dietary calcium, skin color and BMI. Conclusion 25(OH)D declined significantly in both black children and white children during winter. CTx significantly increased during winter in black children compared to white children, suggesting increased rates of resorption in black children during winter. Benefits of enhancement of wintertime vitamin D status on bone health need further exploration.